1987
DOI: 10.1159/000298848
|View full text |Cite
|
Sign up to set email alerts
|

Human Follicular Fluid Levels of Calcium, Copper and Zinc

Abstract: Human follicular fluid was collected under laparoscopic vision from 33 follicles in patients stimulated with clomiphene-human menopausal gonadotrophin in an IVF programme. Thirty-one oocytes were obtained from 26 follicles from which clear follicular fluid was obtained, and 16 oocytes fertilized and cleaved. The follicular fluid was analysed for calcium, copper and zinc using atomic absorption spectroscopy. The mean levels of calcium, copper and zinc were 86.9 ± 11.6, 1.16 ± 0.29, and 0.72 ± 0.12 µg/ml, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
2
16
1
Order By: Relevance
“…Similarly, Zn media supplementation (3.6-19 μmol) was associated with better quality mouse embryos [38,39], yet higher concentrations (25 μmol) were embryotoxic [39]. Still, an earlier study of 33 human follicles found no association between Zn and oocyte fertilization during IVF [40]. The mean FF Zn (720 μg/L) in that study was higher than the maximum value measured in this study (687 μg/L).…”
Section: Discussioncontrasting
confidence: 64%
“…Similarly, Zn media supplementation (3.6-19 μmol) was associated with better quality mouse embryos [38,39], yet higher concentrations (25 μmol) were embryotoxic [39]. Still, an earlier study of 33 human follicles found no association between Zn and oocyte fertilization during IVF [40]. The mean FF Zn (720 μg/L) in that study was higher than the maximum value measured in this study (687 μg/L).…”
Section: Discussioncontrasting
confidence: 64%
“…However, the study measured only plasma zinc concentrations, which only reflect short term zinc turnover. A further study of the zinc levels in the follicular fluid of 33 follicles taken during ART found no difference in the levels between follicles of different sizes, and those that yielded oocytes that were successful and unsuccessful in fertilisation [40], but no additional confirmatory studies have been undertaken.…”
Section: Discussionmentioning
confidence: 97%
“…Studies on the effects of zinc deficiency in women with IVF are scarce. Ng et al [10] investigated zinc levels in follicular fluid of 33 women undergoing IVF in Singapore and did not observe any correlation between follicular fluid zinc concentration and follicle volume. Jameson [19] reported longstanding infertility in seven, normal sexually developed women with celiac disease.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, magnesium plays a protective role in the developing fetus brain [9]. Calcium has a basic function in neurotransmitter secretion and magnesium blocks the entrance of calcium into cells [10]. Enzymatic and nonenzymatic antioxidants are also essential for inhibition of free radical production related to oocyte maturation and rupture [11][12][13].…”
Section: Introductionmentioning
confidence: 99%